The Influence Of Marketing Strategy And Customer Satisfaction On Customer Loyalty at PT. Mitragraha Inti Utama - Indriani, Fuji Aldiena; Insani, Siti (Pascasarjana STIE Miftahul Huda, 2025)
This research investigates the impact of marketing strategies and customer satisfaction on customer loyalty at PT Mitragraha Inti Utama. In today’s highly competitive business environment, maintaining customer retention presents a substantial challenge for organizations. Strategic marketing efforts and high levels of customer satisfaction are widely acknowledged as key drivers of customer loyalty. Employing a quantitative research design, the study utilizes a survey method by distributing structured questionnaires using a Likert scale to 100 customers of PT Mitragraha Inti Utama. The collected data were analyzed using multiple linear regression to examine the effect of each independent variable. The findings reveal that marketing strategy significantly and positively influences customer loyalty. Likewise, customer satisfaction also demonstrates a significant and positive relationship with customer loyalty. Furthermore, when considered simultaneously, both marketing strategy and customer satisfaction significantly contribute to enhancing customer loyalty. The research findings indicate that marketing strategies have a positive and significant impact on customer loyalty. Based on the determination test, marketing strategies and customer satisfaction contribute 90.7% to customer loyalty at PT Mitragraha Inti Utama, while the remaining percentage is influenced by other variables not examined in the study.These results highlight the critical need for companies to continuously refine their marketing strategies and uphold service excellence in order to foster customer satisfaction and secure long-term loyalty.